Assessing the Relationship between CO2 Emissions, Renewable Energy, Trade Openness and Economic Growth: MENA Countries Analysis - Yahyaoui, Ismahen; Ghandri, Mohamed (International Journal of Energy Economics and Policy, 2024)
This study employed the FMOLS and DOLS models to examine the impact of renewable energy, trade openness and economic growth on CO2 emissions in MENA countries over the period 1990-2023. Furthermore, we employ SGMM approach in order to robustify DOLS and FMOLS results. Our findings reveal that the renewable energy promotes the environmental quality by decreasing the CO2 emissions in the MENA countries. However, the economic growth increases the carbon emissions. The study reveals also that instead of the conventional U-shaped EKC hypothesis, there is the inversed U-shaped relationship between CO2 emissions and economic growth in the long run. For the trade openness, it has a negative effect on CO2 emissions, in the SGMM model. However, our findings in the FMOLS and DOLS show that it increases the CO2 emissions in the long run. Then this paper suggests that MENA policy makers should maximise the use of renewable energy and ensure the efficient utilization of GDP and trade openness in order to minimise the level of CO2 emissions.